Concentration Effect of Germanium Dioxide on the Spectroscopic Properties and Laser Performance of Er3+/Yb3+ Co-Doped Phosphate Glasses. (4th December 2020) - Zhang, Bingtao; Zhao, Zigang; Gong, Yanbing; Ren, Yifan; Liu, Minzhe; Yan, Wei; Wang, Yong; Chen, Guihuan
Abstract : The Er 3+ /Yb 3+ co-doped phosphate glasses with GeO2 modification (PGs) were successfully prepared by melt-quenching method. Their physical parameters were investigated such as density, refractive index, glass transition temperature and coefficients of thermal expansion. The phenomenological intensity parameters Ω t ( t = 2, 4, 6) of the PGs have been calculated by the Judd-Ofelt theory. The relationship between optical properties and GeO2 concentration was discussed in this work. The laser experiment using PG10 (GeO2 10 mol% modified phosphate glass with Er 3+ /Yb 3+ ratio of 0.5/2) was carried out. The research results indicate that the introduction of GeO2 results in a large absorption and emission cross-section, a long lifetime, a high quantum efficiency, and an excellent laser performance. All these advantages could also portend an optimized method for improving spectroscopic properties in other constituent Er 3+ /Yb 3+ co-doped phosphate glass by introducing GeO2 .